Early detection of radiation-induced heart disease using 99mTc-MIBI SPECT gated myocardial perfusion imaging in patients with oesophageal cancer during radiotherapy. Issue 2 (May 2015) - Zhang, Peng; Hu, Xudong; Yue, Jinbo; Meng, Xue; Han, Dali; Sun, Xindong; Yang, Guoren; Wang, Shijiang; Wang, Xiaohui; Yu, Jinming
Abstract Background and purpose The primary aim of this prospective study was to investigate the value of 99mTc-methoxyisobutylisonitrile (MIBI) single photon emission computed tomography (SPECT) gated myocardial perfusion imaging (GMPI) in the detection of radiation-induced heart disease (RIHD) as early as during radiotherapy (RT) for oesophageal cancer (EC). The second aim was to analyse the correlation between cardiac toxicity and the dose–volume factors. Materials and methods The 99mTc-MIBI SPECT GMPI was performed both pre-RT and during RT (40 Gray). The results of the SPECT were quantitatively analysed with QGS/QPS software and read by two experienced nuclear medicine physicians. The correlation between the changes in the SPECT parameters and the RT dosimetric data was analysed. Results Eighteen patients with locally advanced EC were enrolled in the study. Compared with the baseline, the imaging during RT showed not only significant decreases in the wall motion (WM) (1/20 segments), wall thickening (WT) (2/20 segments), end-diastolic perfusion (EDP) (5/20 segments) and end-systolic perfusion (ESP) (8/20 segments) (p < 0.05) but also a significant increase in the heart rate (74.63 ± 7.79 vs 81.49 ± 9.90, p = 0.036). New myocardial perfusion defects were observed in 8 of the 18 patients. The V37–V40 was significantly higher (p < 0.05) in the patients with the new perfusion defects during RT than in the patients who did not exhibit these defects. Conclusions Radiotherapy for EC induces cardiac damage from an early stage. 99mTc-MIBI SPECT GMPI can detect the occurrence of cardiac impairment during RT. The WM, WT, EDP and ESP may be valuable as early indicators of RIHD. The percentage of the heart volume that receives a high dose is an important factor that is correlated with RIHD.